Accounting practices in Malaysia - Goh,, Joon Hai (Penerbit Universiti Kebangsaan Malaysia, 1982)
This paper comments on the significant accounting practices adopted in Malaysia against the Standards set by the International Accounting Standards Committee (lASC). An attempt is made to analyse any departure from the IAS and the reasons thereof. as well as to suggest means of minimizing the diversities in future.